(untitled) (Journal of the Bangladesh Agricultural University, 2012)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during November 2008 to April 2009 to evaluate the effect of row and hill spacings on the yield of rice (cv. BRRI dhan45) under aerobic system of cultivation in boro season. Aerobic system is a new water efficient rice production system where the crop is grown by direct seeding on well prepared dry beds and also by maintaining the soil moisture at field capacity during the growing period. The experiment consisted of two row to row spacings viz. 20 and 25 cm, and five hill to hill spacings viz., 2.5, 5, 10, 15 and 20 cm. The trial was laid out in a randomized complete block design with 3 replications. Results revealed that the crop sown at 25 cm ×15 cm produced the highest grain yield of 5.69 t ha-1 whereas the lowest grain yield of 2.11 t ha-1 was found with 20 cm × 2.5 cm spacing. The present study concludes that the highest grain yield of BRRI dhan45 during boro season under aerobic system of cultivation could be achieved by sowing at 25 cm ×15 cm spacing. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12037 J. Bangladesh Agril. Univ. 10(1): 3942, 2012